2004
DOI: 10.1136/adc.2003.029306
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of maternal dietary iodine insufficiency in the north east of England: implications for the fetus

Abstract: Background: Maternal subclinical hypothyroidism is a cause of poor neurodevelopment outcome in the offspring. Although iodine deficiency is the most common cause of hypothyroidism world wide, there are no screening programmes for it in the United Kingdom where the population is assumed to be iodine replete. Objective: To determine the prevalence of reduced iodine intake by measuring urinary iodide concentrations in pregnant and non-pregnant women from the north east of England. Methods: Urinary iodide excretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
68
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 19 publications
9
68
0
Order By: Relevance
“…Exposure to environmental factors such as chemicals or increasing levels of other risk factors such as maternal iodine deficiency or high prenatal iodine exposures [27] or low birth weight infants [28], may be suggested by an increasing temporal trend, whereas infections or seasonally varying dietary factors or chemical exposures, such as dioxin and polychlorinated biphenyl [29], may be suggested by evidence of seasonal variation in the number of cases. The potential role of a suboptimal maternal iodine status in some parts of the North of England should be highlighted and clearly warrants further study [30]. We found little evidence of seasonal variation of elevated TSH levels in newborns, in line with a number of previous reports of no seasonality [4,9,[12][13][14].…”
Section: Discussionsupporting
confidence: 74%
“…Exposure to environmental factors such as chemicals or increasing levels of other risk factors such as maternal iodine deficiency or high prenatal iodine exposures [27] or low birth weight infants [28], may be suggested by an increasing temporal trend, whereas infections or seasonally varying dietary factors or chemical exposures, such as dioxin and polychlorinated biphenyl [29], may be suggested by evidence of seasonal variation in the number of cases. The potential role of a suboptimal maternal iodine status in some parts of the North of England should be highlighted and clearly warrants further study [30]. We found little evidence of seasonal variation of elevated TSH levels in newborns, in line with a number of previous reports of no seasonality [4,9,[12][13][14].…”
Section: Discussionsupporting
confidence: 74%
“…The increasing contribution of milk iodine is likely to be a major reason why estimated dietary iodine intakes in the UK increased between 1952 and 1982 from 80 mg to 255 mg/d (76) . However, several UK authors have suggested that the increasing trend to replace iodine compounds used in the dairy and baking industries with non-iodine alternatives may be decreasing iodine intakes, similar to the situation that has occurred in Australia (77)(78)(79)(80)(81)(82) . If adventitious dietary iodine falls, the population may be vulnerable to iodine deficiency because iodised salt makes up < 5% of all salt consumed in the UK and the Republic of Ireland (77) .…”
Section: The Uk and The Republic Of Irelandmentioning
confidence: 99%
“…Recent measurement of the iodine content in retail salt (thirty-six samples) in Cardiff (Wales) has shown iodine concentrations to be undetectable in thirty-two samples, with two samples, labelled as iodised, containing approximately 20 mg iodine/kg (77) . Limited data from Scotland (78) and north-east England (79) suggest many pregnant women are iodine deficient. In a study in Middlesbrough (north-east England) in 2000-2001 pregnant women attending the antenatal clinic at 15 weeks of gestation (n 227) and non-pregnant age-matched controls (n 227) were enrolled (79) .…”
Section: The Uk and The Republic Of Irelandmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine deficiency has been demonstrated in the UK in recent years in women of childbearing age (1)(2)(3) and pregnant women (4)(5)(6)(7) . The UK is now among the top ten iodine-deficient countries worldwide (8) , based on data from the 2011 national survey of teenage schoolgirls that revealed mild iodine deficiency in the cohort (1) .…”
mentioning
confidence: 99%